Symphonie du millénaire : The Sacred in the Profane - Goldman, Jonathan (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractIn this article, Jonathan Goldman makes some personal observations about the Symphonie du Millénaire and its possible cultural meaning. Rejecting the distinction between sacred and profane, between religious and secular, he attempts to analyze this work, armed with score and recording, as a cultural object of considerable significance.